Rural Development and Hidden Poverty - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Développement Rural - La Pauvreté Cachée, 374pp ISBN 2-86537252 9 Editions Karthala 22-24 boulevard Arago 75013 Paris - FRANCE